Sustainable university development through sustainable human resources and corporate entrepreneurship: The role of sustainable innovation and work environment - Janusz Grabara; Hafezali Iqbal Hussain; Marek Szajt (Amfiteatru Economic Journal, 2020)
Objective of the current study is to examine the role of sustainable human resource (HR) and corporate entrepreneurship on sustainable university development in Poland. The role of sustainable innovation and environment is also examined. For this purpose, data were gathered by using a questionnaire survey. Questionnaires were distributed among the employees of universities in Poland. In addition, cluster sampling was used for data collection. For data analysis, Structural Equation Modelling (SEM) was used through Partial Least Square (PLS). Results of the study revealed that sustainable HR and corporate entrepreneurship has significant role to enhance university sustainability through sustainable innovation. It is found that sustainable HR and corporate entrepreneurship has positive effect on sustainable innovation which leads to the sustainable university development. Moreover, working environment among the universities also has important role to enhance university sustainability through sustainable innovation activities. The study findings have significance for policy-makers as it clearly emphasizes on sustainable HR and organizational entrepreneurship's critical role in the successful implementation of innovation activities to enhance sustainable university development.
Keywords: I23; Q55; Q56; 330; sustainable university development; sustainable HR; corporate entrepreneurship; sustainable innovation; environment